Squeeze Film Lubrication between Rough Poroelastic Rectangular Plates with Micropolar Fluid: A Special Reference to the Study of Synovial Joint Lubrication. (30th December 2012) - Naduvinamani, N. B.; Savitramma, G. K.
Abstract : The effects of surface roughness and poroelasticity on the micropolar squeeze film behavior between rectangular plates in general and that of synovial joints in particular are presented in this paper. The modified Reynolds equation, which incorporates the randomized surface roughness structure as well as elastic nature of articular cartilage with micropolar fluid as lubricant, is derived. The load-carrying capacity and time of approach as functions of film thickness during normal articulation of joints are obtained by using Christensen stochastic theory for rough surfaces with the assumption that the roughness asperity heights are to be small compared to the film thickness. It is observed that the effect of surface roughness has considerable effects on lubrication mechanism of synovial joints.